(-3/2)(y-8)-1/6y

Simple and best practice solution for (-3/2)(y-8)-1/6y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-3/2)(y-8)-1/6y equation:


y in (-oo:+oo)

(-3/2)*(y-8)-((1/6)*y) = 0

(-3/2)*(y-8)+(-1/6)*y = 0

-3/2*(y-8)-y/6 = 0

(-3/2*6*(y-8))/6-y/6 = 0

-3/2*6*(y-8)-y = 0

72-10*y = 0

(72-10*y)/6 = 0

(72-10*y)/6 = 0 // * 6

72-10*y = 0

72-10*y = 0 // - 72

-10*y = -72 // : -10

y = -72/(-10)

y = 36/5

y = 36/5

See similar equations:

| 3/4(9)-8 | | 9x^2-65x-56=0 | | -46-10x=-136 | | 5a=3a-10 | | -6c+5=-13 | | 6x1/10 | | 85=-6x+4x | | 10m^5x^8-15m^3z^10=0 | | 3/5-(-10/11) | | 20x-5x+2=190 | | 3.9x=53 | | -4(x+9)-41=5-58 | | 3(3c-1)-6=4c+6 | | 9-3x-2x=6 | | -7y+6=8y+2 | | (2x^2-128)/(x-8) | | x=16/Sin55 | | -5-1.5a=-5.8a-6.29 | | 6e^5x=1980 | | x-2(3x-7)=0 | | 2x-1=256/5 | | 3x^2+54x+0=0 | | 6y+3+(5y+7)=13y-2 | | -40=3x+24+x | | -9(1+7x)-6(-7-x)=36 | | 10x=7(x+21) | | (2x^4)+(x^2)-1=0 | | l=2(2lw+wh) | | 65=2t-15t | | -8x=-4(2x+1) | | (x-6)(5x+7)= | | 3=8/7d=-1 |

Equations solver categories